Research on the steel corrosion inhibition of green tea leaf extract in a simulated sea water environment - Ngo Minh Tien; Dao Thi Lan Huong; Nguyen Thi Thoa; Nguyen Van Chanh; Nguyen Thi Hoai Phuong (Journal of Military Science and Technology, 2025)
In this paper, the effect of polyphenol compounds extracted from green tea leaves to inhibit CT3 steel corrosion in a simulated sea water environment was studied. The corrosion inhibitor is evaluated through some specifications: electrochemical corrossion and salt spray corrosion test by the B117-16 standard. A scanning electron microscope (SEM) and the salt-sprayed steel plate surface observation were used to evaluate the level of corrosion. The CT3 steel soaked in polyphenol solutions with various concentrations and times showed different corrosion resistance in marine conditions. At the polyphenol concentration of 1.5 mg in 1 liter solution, the corrosion rate of CT3 steel is reduced from 0.057 mm/year compared to 0.113 mm/year in the 3.5% NaCl solution without polyphenol, and soaking CT3 steel for 45 minutes in polyphenol : water : ethanol solution (1 g : 90 ml : 910 ml) gives the best resistance to salt spray corrosion.